Treatment modalities for post-COVID-19 anosmia and hyposmia: a systematic review (Research, Society and Development, 2022)
Objective: To analyze the main treatment strategies for post-COVID-19 anosmia and hyposmia. Methods: Systematic review guided by PRISMA. The studies were searched between February and September 2021, in the electronic data sources of Pubmed, Cochrane (CENTRAL), LitCOVID and BVS. Inclusion criteria were clinical trials published from December 2019 to September 2021, on patients with maintenance of post-COVID-19 olfactory disorders, and the main existing treatment strategies were analyzed. Exclusion criteria were studies published before December 2019, performed in patients under 18 years of age and other types of study designs. Risk of bias analysis was performed using the ROB 2.0 tool for randomized clinical trials, and ROBINS-I for non-randomized trials. Results: Five articles were selected. A total of 237 patients with maintenance of post-COVID-19 olfactory disorders were evaluated. The follow-up of the patients' olfactory function ranged from a minimum of 3 weeks to a maximum of 10 weeks. The treatment modalities that demonstrated the greatest benefits to the olfactory function of these patients were corticosteroids and olfactory training. Conclusion: Treatment for post-COVID-19 anosmia and hyposmia should be started two weeks after the onset of olfactory symptoms. The use of corticosteroids and the practice of olfactory training are the treatment modalities that presented the best evidence regarding the recovery of olfactory function. Other less conventional modalities lack more robust evidence and cannot yet be recommended.